Method for improving catalytic degradation of PET (Polyethylene Terephthalate) plastic by cutinase

By preparing polymer agglomeration phase and microorganism-induced expression of enzymes, the problem of insufficient activity of enzyme-catalyzed degradation of PET plastics was solved, and a more efficient degradation effect of PET plastics was achieved.

CN119709893AActive Publication Date: 2025-03-28SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411841378.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

In the prior art, the activity of enzyme catalyzed degradation of PET plastics is insufficient, making it difficult to effectively improve the degradation efficiency of PET plastics.

Method used

LCC-I CCG-218Y enzyme was prepared by preparing polymer system condensed phase, regulating the type and molar ratio of the condensed phase, and combining microbial induced expression, and using a shocker to uniformly mix the enzyme and PET wafers and conduct a warming reaction to improve the degradation efficiency of PET plastic.

Benefits of technology

This method significantly improves the degradation efficiency of PET plastics under mild reaction conditions, is simple to operate, has low equipment requirements, and is faster than that of traditional phosphate buffers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709893A_ABST
    Figure CN119709893A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving cutinase catalytic degradation of PET (Polyethylene Terephthalate) plastics, which comprises the following steps: preparing a macromolecular condensed phase, and collecting a concentrated phase of the condensed phase in a centrifugal manner; adding an LCC-ICCG-218Y enzyme solution and a PET solid into the concentrated phase, and oscillating to enable the LCC-ICCG-218Y enzyme solution and the PET solid to be uniformly distributed in a reaction system; reacting in an oil bath at 40-72 DEG C, collecting a reaction solution, and characterizing a degradation product through ultraviolet rays. Compared with a phosphate buffer solution, the method has the advantage that the degradation rate of the PET plastic at 40 DEG C and 50 DEG C is finally doubled compared with that of a buffer solution system. According to the method, a simple method for improving enzymolysis of the PET plastic is established, only the reaction microenvironment of the enzyme is regulated and controlled, complex protein modification and enzyme immobilization means are not needed, and the method has certain application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of enzyme reaction microenvironment regulation and control, and particularly relates to a method for improving the catalytic degradation of PET plastic by cutinase. Background Art

[0002] Polyethylene terephthalate (PET plastic) is a common plastic known for its high mechanical properties, good processing properties and good chemical stability. It is often used as a raw material for various packaging bottles. However, due to its high temperature resistance, chemical corrosion resistance and difficulty in biodegradation, PET plastic has brought serious environmental problems. It is urgent to find a method to properly dispose of plastic waste. Compared with traditional physical recycling and chemical depolymerization, enzymatic depolymerization has mild process conditions, does not require hazardous chemicals and expensive equipment, and the degradation products can be recycled to avoid secondary pollution. It is considered to be an ideal PET depolymerization method. A thermostable cutinase (LCC) derived from leaf and branch compost can cut ester bonds and decompose PET into monomers terephthalic acid (TPA) and ethylene glycol (EG). Jeffrey D.Martell et al. found that the H218Y mutant of LCC-I CCG can improve the binding of the enzyme to the PET substrate and improve the depolymerization kinetics of PET.

[0003] As a biological macromolecule, protein has a complex structure. With its advantages of high efficiency and specificity, it undertakes the important task of catalyzing metabolism. Enzymes are easily inactivated under harsh conditions, such as high temperature, polar solvents, extreme pH values, proteases and other environmental factors. Since there are many factors affecting the catalytic activity of enzymes, relevant means are needed to improve enzyme activity. Currently, the commonly used regulatory means include carrier immobilization modification, chemical covalent modification and protein engineering modification. Carrier immobilization modification can ensure high enzyme load, but at the same time it may cause changes in enzyme biological function due to the fragility of the enzyme; the chemical covalent modification process requires the enzyme to have high tolerance to the reaction environment; protein engineering modification requires rational design of proteins, and regulates the enzyme active site or substrate / product channel structure to improve enzyme activity, which has high technical barriers. Summary of the invention

[0004] The present invention aims to overcome the insufficient activity of the prior art enzyme-catalyzed degradation of PET plastics and invent a method for improving the degradation of PET plastics by cutinase.

[0005] The technical solution of the present invention to achieve the above-mentioned purpose is as follows:

[0006] A method for improving the degradation of PET plastic by cutinase, comprising the following steps:

[0007] S1. Prepare a polymer system condensed phase, adjust the viscosity of the system with KCl solution, and collect the concentrated phase of the condensed phase by centrifugation;

[0008] S2, using microbial induction expression to prepare LCC-I CCG-218Y enzyme solution, and obtaining pure enzyme solution through affinity chromatography of the expressed product;

[0009] S3, using a puncher to prepare the PET solid into small round pieces, and processing them with scissors;

[0010] S4, adding the LCC-I CCG-218Y enzyme solution and the PET disc into the dense phase, using an oscillator to mix the system evenly to obtain a mixed solution, and heating it to react;

[0011] S5, collecting the reaction solution and diluting it with KCl solution;

[0012] S6. Take the supernatant and detect the product by ultraviolet absorption.

[0013] Furthermore, the polymer condensed phase components are two of polylysine, polyglutamic acid, polydiallylpropylenedimethylammonium chloride, and sodium polyacrylate, in a molar ratio of 40:100, 70:100, or 100:100;

[0014] Furthermore, the component concentration of the dense phase is 50-150 mM, the pH value is 5-10, and contains 0.05-0.1 mol / L phosphate buffer;

[0015] Furthermore, the concentration of the KCl solution is 1 mol / L.

[0016] Furthermore, the enzyme concentration in the mixed solution is 6nmol / L-2μmol / L.

[0017] Furthermore, the PET solid is a sheet-like film with a crystallinity of 4-7% and a thickness of 0.25 mm.

[0018] Furthermore, the mass volume ratio of the PET solid to the dense phase is 2-20 g / L.

[0019] Furthermore, the reaction temperature is 40-72° C.; the reaction stirring speed is 0-600 rpm.

[0020] Further, the enzyme solution is cutinase LCC, and one of its mutants I CCG and 218Y;

[0021] Preferably, the enzyme solution is LCC-I CCG-218Y, and the LCC-I CCG-218Y protein is produced by inducing microbial expression, and an aqueous solution of the LCC-I CCG-218Y enzyme is obtained after purification.

[0022] The sequence of LCC-WT (WT) in the present invention is as follows:

[0023] MSNPYQRGPNPTRSALTADGPFSVATYTVSRLSVSGFGGGVIYYPTGTSLTFGGI

[0024] AMSPGYTADASSLAWLGRRLASHGFVVLVINTNSRFDYPDSRASQLSAALNYLRTSSPS

[0025] AVRARLDANRLAVAGHSMGGGGTLRIAEQNPSLKAAVPLTPWHTDKTFNTSVPVLIVGA

[0026] EADTVAPVSQHAIPFYQNLPSTTPKVYVELDNASHFAPNSNNAAISVYTISWMKLWVDN

[0027] DTRYRQFLCNVNDPALSDFRTNNRHCQLEHHHHHH

[0028] The sequence of LCC-ICCG (ICCG) is as follows:

[0029] MSNPYQRGPNPTRSALTADGPFSVATYTVSRLSVSGFGGGVIYYPTGTSLTFGGI

[0030] AMSPGYTADASSLAWLGRRLASHGFVVLVINTNSRFDGPDSRASQLSAALNYLRTSSPS

[0031] AVRARLDANRLAVAGHSMGGGGTLRIAEQNPSLKAAVPLTPWHTDKTFNTSVPVLIVGA

[0032] EADTVAPVSQHAIPFYQNLPSTTPKVYVELCNASHIAPNSNNAAISVYTISWMKLWVDN

[0033] DTRYRQFLCNVNDPALCDFRTNNRHCQLEHHHHHH

[0034] The sequence of LCC-ICCG-218Y is as follows:

[0035] MSNPYQRGPNPTRSALTADGPFSVATYTVSRLSVSGFGGGVIYYPTGTSLTFGGI

[0036] AMSPGYTADASSLAWLGRRLASHGFVVLVINTNSRFDGPDSRASQLSAALNYLRTSSPS

[0037] AVRARLDANRLAVAGHSMGGGGTLRIAEQNPSLKAAVPLTPWHTDKTFNTSVPVLIVGA

[0038] EADTVAPVSQYAIPFYQNLPSTTPKVYVELCNASHIAPNSNNAAISVYTISWMKLWVDNDTRYRQFLCNVNDPALCDFRTNNRHCQLEHHHHHH.

[0039] Compared with the prior art, the present invention has the following advantages and effects:

[0040] 1. The present invention only needs to adjust the type and molar ratio of the condensed phase and the dense phase, as well as the reaction temperature and stirring speed, and has simple operation, mild reaction conditions and low equipment requirements;

[0041] 2. For the enzyme-catalyzed degradation reaction of PET plastic, the reaction rate of the condensed phase and dense phase reaction environment provided by the present invention is faster than that of the phosphate buffer solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is the kinetic curve of PET degradation by enzyme in concentrated phase and phosphate environment at 40°C;

[0043] Figure 2 It is the kinetic curve of enzyme degradation of PET in concentrated phase and phosphate environment at 50°C;

[0044] Figure 3 The effect of different concentrations on the enzyme-catalyzed degradation of PET plastics;

[0045] Figure 4 The effect of different concentrations on the enzyme-catalyzed degradation of PET plastic. DETAILED DESCRIPTION

[0046] The present invention will be further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.

[0047] Example 1

[0048] Step 1 Extraction of the dense phase of the condensed phase comprises the following steps:

[0049] Component a (table below) with a concentration of 400 mM and a pH value of 8 is mixed with component b (table below) with a concentration of 400 mM and a pH value of 8 at a molar ratio of 40:100, 70:100 or 100:100, and 1 mol / L KCl solution is added to adjust the viscosity of the system. After centrifugation at 8000 x g for 4 min, the supernatant is completely removed to obtain a concentrated phase. The above-mentioned concentrated phase contains 0.05-0.1 M phosphate buffer;

[0050]

[0051] Step 2: Pretreatment of the substrate PET, comprising the following steps:

[0052] Amorphous PET solid purchased from Goodfellowe was prepared into discs with a diameter of about 0.03-0.8 cm using a hole puncher and processed with scissors. The PET solid was a sheet-like film with a crystallinity of about 4-7% and a thickness of 0.25 mm.

[0053] Step 3 Expression, purification and identification of cutinase (LCC-I CCG-218Y)

[0054] Take 1-2 μL of the recombinant plasmid containing the LCC-I CCG-218Y gene, add it to 100 μL of E.coli BL21 (DE3) competent cells thawed on ice, mix gently and place in an ice bath for 15-20 minutes, take it out and place it in a 42°C constant temperature water bath for 90 seconds, then immediately place in an ice bath for 5 minutes, add 1 mL of LB medium (without antibiotics), shake and recover in a shaker for 1 hour (37°C, 170-250rpm). After recovery, take 100-300 μL and apply it on LB solid medium containing kanamycin (50 μg / mL) resistance, and culture it at 37°C overnight. The resulting single colony is E.coli BL21 (DE3)-pET-28b (+)-LCC-I CCG-218Y. Pick a single colony and culture it in LB containing kanamycin (50 μg / mL) for 10-16 hours. When the OD value reaches 0.6-0.8, the bacterial solution is inoculated into LB medium containing kanamycin (50 μg / mL) at a ratio of 1:100, and the bacterial solution is expanded and cultured at 37°C and 170-250rpm until the bacterial solution OD600 is 0.6-0.8. After cooling to room temperature, IPTG with a final concentration of 0.2mmo l / L is added, and the expression is induced at 18°C ​​and 225rpm for 20 hours. The bacterial cells after induced expression are collected by centrifugation at 4°C and 6000rpm for 20min, and the cells are resuspended with ti rs-HCl buffer with a pH of 7.5-8. The resuspended bacterial solution is crushed for 30min using an ultrasonic crusher at 140-220W, working for 5s, and stopping for 5.5s. The supernatant is obtained as a crude enzyme solution by centrifugation at 15000xg at 4°C for 30min, and then purified by nickel column affinity chromatography to obtain LCC-I CCG-218Y enzyme solution.

[0055] Step 4: The method for LCC-I CCG-218Y enzyme-catalyzed degradation of PET plastics comprises the following specific steps:

[0056] In a 1.5 ml glass bottle, add PH=8, 0.1 M phosphate buffer prepared with ultrapure water, a PET disc weighing 2.4 mg and a thickness of 0.25 mm, and a LCC-I CCG-218Y enzyme solution with a final concentration of 0.1 μmol / L, and mix them evenly to obtain a reaction solution. In an oil bath at 50°C, the reaction was carried out at a speed of 600 rpm for 7 days, and the reaction solution was collected at regular intervals to detect degradation products by ultraviolet light.

[0057] Step 5: Calculation of degradation products, including the following steps:

[0058] The concentration of the product terephthalic acid (TPA) was calculated based on its absorbance at 240-260 nm, and a standard curve was drawn for TPA. In the reference, the mass volume ratio of substrate PET to reaction solution was 2 g / L, and 10.4 mM TPA was completely converted. This concentration was taken as 100% PET degradation rate to characterize the degradation effect.

[0059] Example 2 Enzymatic degradation of PET plastics in concentrated phase and phosphate buffer solution environments at 40°C

[0060] The concentrated phase with a molar concentration ratio of 40:100, LCC-I CCG-218Y enzyme solution and a PET disc with a weight of 2-20 mg and a thickness of 0.25 mm were mixed evenly to obtain a mixed solution. The LCC-I CCG-218Y enzyme concentration in the mixed solution was 0.1 μmol / L. The mixed solution was placed in an oil bath at 40°C and 600 rpm for 1-18 days. The reaction solution was collected at regular intervals and the absorbance of the product was detected by ultraviolet light. The results are as follows Figure 2 After 18 days of reaction, the degradation rate of the concentrated phase was nearly twice that of the buffer solution, which were 65.5±3.92% and 37.23±0.72%, respectively.

[0061]

[0062] Example 3 Enzymatic degradation of PET plastics in concentrated phase and phosphate buffer solution environments at 50°C

[0063] The concentrated phase (see the table below) with a molar concentration ratio of 40:100, LCC-I CCG-218Y enzyme solution and a PET disc with a weight of 2.4 mg and a thickness of 0.25 mm were mixed evenly to obtain a mixed solution. The LCC-I CCG-218Y enzyme concentration in the mixed solution was 0.1 μmol / L. The mixed solution was placed in an oil bath at 50°C and 600 rpm for 5 days. The reaction solution was collected at regular intervals and the absorbance of the product was detected by ultraviolet light. The results are shown in Figure 3 After 5 days of reaction, the degradation rates of concentrated phase and phosphate buffer were 95±2.41% and 42.27±7.21%, respectively, indicating that the concentrated phase significantly improved the degradation effect of cutinase LCC-I CCG-218Y on PET plastic.

[0064]

[0065]

[0066] Example 4 Effect of different concentrations on enzyme-catalyzed degradation of PET plastics

[0067] The concentrated phase (see the table below), LCC-I CCG-218Y enzyme solution and a PET disc weighing 2.4 mg and having a thickness of 0.25 mm were mixed evenly to obtain a mixed solution. The LCC-I CCG-218Y enzyme concentration in the mixed solution was 0.1 μmol / L. The mixed solution was placed in an oil bath at 50°C and 600 rpm for 7 days. The reaction solution was collected at regular intervals and the absorbance of the product was detected by ultraviolet light. The results are shown in FIG. Figure 4 It can be seen that the degradation rate of PET plastic catalyzed by enzymes in different concentrated phases is different.

[0068]

[0069] Example 5 Effects of different concentration ratios on enzyme-catalyzed degradation of PET plastics

[0070] Take a polydiallylpropyldimethylammonium chloride aqueous solution with a concentration of 400mM and a pH value of 8 and a sodium polyacrylate aqueous solution with a concentration of 400mM and a pH value of 8, mix the LCC-I CCG-218Y enzyme solution and a PET disc with a weight of 2.4mg and a thickness of 0.25mm in a molar ratio of 40:100, 70:100 or 100:100, and mix them evenly to obtain a mixed solution. The LCC-I CCG-218Y enzyme concentration in the above mixed solution is 0.1μmol / L, and the mixed solution is oil bathed at 50℃ and 600rpm for 5 days, and the reaction solution is collected at intervals, and the absorbance of the product is detected by ultraviolet. After reacting at 50℃ for 5 days, the effect of enzyme-catalyzed degradation of PET plastic varies depending on the concentration ratio of the concentrated phase.

[0071]

[0072] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for improving the catalytic degradation of PET plastic by cutinase, characterized in that: The following steps are involved: S1. Prepare a polymer system condensed phase, adjust the viscosity of the system with KCl solution, and collect the concentrated phase of the condensed phase by centrifugation; S2, using microbial induction expression to produce LCC-ICCG-218Y enzyme, and obtaining pure enzyme solution by affinity chromatography after ultrasonication and centrifugation of the supernatant; S3, cutting the PET solid into small pieces; S4, adding the LCC-ICCG-218Y enzyme solution and the PET flakes into the dense phase, using an oscillator to mix the system evenly to obtain a mixed solution, and heating the mixture to react; S5, collecting the above reaction solution and diluting it with KCl solution; S6. Take the supernatant and detect the product by ultraviolet absorption.

2. The method for improving the catalytic degradation of PET plastic by cutinase according to claim 1, characterized in that: In S1, the components of the polymer condensed phase are two of polylysine, polyglutamic acid, polydiallylpropylenedimethylammonium chloride, and sodium polyacrylate.

3. The method for improving the catalytic degradation of PET plastic by cutinase according to claim 2, characterized in that: The components of the polymer condensed phase are composed in a molar ratio of 40:100, 70:100 or 100:

100.

4. The method for improving the catalytic degradation of PET plastic by cutinase according to claim 1, characterized in that: In S1, the component concentration of the dense phase is 50-150 mM, the pH value is 5-10, and it contains 0.05-0.1 mol / L phosphate buffer.

5. The method for improving the catalytic degradation of PET plastic by cutinase according to claim 1, characterized in that: In S1, the KCl concentration is 0.5-3 mol / L.

6. The method for improving the catalytic degradation of PET plastic by cutinase according to claim 1, characterized in that: In S1, the centrifugation speed and time are 5000-9000xg, 4-8min.

7. The method for improving the catalytic degradation of PET plastic by cutinase according to claim 1, characterized in that: In S4, the concentration of LCC-ICCG-218Y enzyme in the mixed solution is: 6nmol / L-2μmol / L.

8. The method for improving the catalytic degradation of PET plastic by cutinase according to claim 1, characterized in that: In S4, the PET solid in the mixed solution is a sheet-like film with a crystallinity of 4-7% and a thickness of 0.1-0.3 mm. The mass volume ratio of the PET solid to the dense phase is 2-20 g / L.

9. The method for improving the catalytic degradation of PET plastic by cutinase according to claim 1, characterized in that: In S4, the reaction temperature in the mixed solution is 40-72°C; the reaction stirring speed is 0-600 rpm; and the reaction days are 1-18.

10. The method for improving the catalytic degradation of PET plastic by cutinase according to claim 1, characterized in that: In S5, the KCl solution is diluted to a UV detection range of 0.2-0.8.

Citation Information

Patent Citations

  • Recombinant escherichia coli for cell surface display PET lytic enzyme, construction and application

    CN106636158A

  • Composition containing hydrolase and polyglutamic acid for prevention and removal of periodontal biofilms

    CN114209818A

  • Enzymatic degradation of polyolefin polymer plastic by using KATG enzyme

    CN115768902A

  • Cutinase variant as well as preparation method and application thereof in plastic degradation

    CN116286727A

  • Cleaning compositions comprising enzymes

    IN201847048708A

Cited By

  • Cutinase mutant gene, protein expressed by same and application of cutinase mutant gene

    CN121896197A